The Health, Functioning and Wellbeing Summary Traffic Light Communication Tool: a survey of families' views. (23rd December 2016) - Ireland, Peter; Horridge, Karen A
Abstract : Aim: To ascertain families' views about the utility of the Health, Functioning and Wellbeing Summary (HFWS) in positively supporting communication in clinics. Method: The HFWS was co‐developed with families and members of the multidisciplinary team. A sequential convenience sample of 60 families who attended clinics in Sunderland, UK in 2015 agreed to participate and answered eight questions about their views on the tool's usefulness. Data were recorded and analysed in Microsoft Excel. Results: All families agreed that they had been able to discuss everything they had wanted to discuss with the doctor. All of the serious concerns that they had recorded on the HFWS had been addressed in the consultation. Most (58 out of 60; 97%) reported that the tool was easy to understand and complete, and 57 out of 60 (95%) reported that it helped them to gather their thoughts about what they wanted to discuss. Consultations that used the tool were thought to better address the needs of 49 out of 60 families (87.1%), than those in which it was not used. Interpretation: The HFWS was acceptable to most families surveyed, improved communication from their perspective, and ensured that the issues that mattered most to them were addressed in medical consultations. The tool has been translated into a number of other languages. Its acceptability and utility in other settings requires further study. What this paper adds: The Health, Functioning and Wellbeing Summary helped families to gather and prioritize their thoughts before consultations. From the families' perspectives, use of the tool improved communication during consultations. The tool ensured that the serious concerns of families were addressed during consultations. Video Podcast:https://youtu.be/Zx4idZRPcy4